Islamic Family Law and the Future of Human Rights: A Bibliometric Analysis, 1928–2025 (Contrarius Series: Law & Social Justice, 2026)
This study traces the development of Islamic Family Law (IFL) literature from 1928 to 2025, focusing on its intersections with the literature on human rights. A title-only search on Scopus returned 299 records. Data cleaning and harmonization, as well as the generation of descriptive indicators, were performed in OpenRefine and BiblioMagika, while VOSviewer was used to construct the keyword co-occurrence and overlay maps. The review is organized around four questions, which concern publication trends and the influential journals for the discipline, the keywords and themes, and the intellectual networks formed through co-occurrence. The findings point to two growth spurts after 2000, a dual source ecology where regionally specific journals underpin volume while globally recognized law journals concentrate influence, and four stable intellectual clusters: marital constructions and gendered rights; doctrines and practices around polygamy and child marriage; the methods of codification that link state law and shariah; and plural legal systems in minority communities. The study provides a concise and reproducible baseline in IFL research and a human rights milieu for future scholarship.